2011
DOI: 10.1002/qj.809
|View full text |Cite
|
Sign up to set email alerts
|

The diurnal cycle of precipitation over the Maritime Continent in a high‐resolution atmospheric model

Abstract: Climate models can exhibit systematic errors in their mean precipitation over the Maritime Continent of the Indonesian archipelago at the heart of the tropical warm pool. These can often be traced back to an erroneous simulation of the diurnal cycle, and can lead to errors in global climate, through planetary wave propagation. Here, we examine the simulation of the diurnal cycle over the Maritime Continent in a series of high-resolution integrations of the UK Met Office atmospheric model, with horizontal resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
210
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(233 citation statements)
references
References 28 publications
23
210
0
Order By: Relevance
“…This is particularly true for the 12 km param model, which has an extremely regular diurnal cycle over the Maritime Continent land areas (Love et al, 2011).…”
Section: Mean Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for the 12 km param model, which has an extremely regular diurnal cycle over the Maritime Continent land areas (Love et al, 2011).…”
Section: Mean Precipitationmentioning
confidence: 99%
“…Cascade seeks to better understand the interaction between tropical convection at the cloud-system scale and larger-scale processes including the MJO, the diurnal cycle of convection over land (Pearson et al, 2010;Love et al, 2011), easterly waves and equatorially trapped waves. To achieve this goal, Cascade employs high-resolution CSRM simulations of the UK Met Office Unified Model (UM) over very large tropical domains and compares them with high-resolution observations, operational analyses provided for the Year of Tropical Convection (YOTC: Waliser and Moncrieff, 2008) and simulations of the same model using parametrized convection.…”
Section: Introductionmentioning
confidence: 99%
“…Love et al (2011) showed that the upward motion over land from daytime propagates as a gravity wave offshore in nighttime. Figure 14 shows meridional sections of the diurnal deviation component of vertical circulation and hourly rainfall in the CTL and NCT runs as 2 h time slices from 0000 LST to 0800 LST.…”
Section: Northwestern Coast Of Borneo At First Peak Stagementioning
confidence: 99%
“…Accordingly, diurnal variations of rainfall over the MC have drawn great climatological interest for several decades [Hendon and Woodberry, 1993;Nitta and Sekine, 1994;Yang and Slingo, 2001;Kikuchi and Wang, 2008]. Many features of these variations have been well documented to date, e.g., the initiation of convection in a mountainous area in the afternoon, the peak of rainfall early in the night, and the movement of rain areas from the mountains to coast or offshore areas around midnight [Nitta and Sekine, 1994;Nesbitt and Zipser, 2003;Mori et al, 2004;Sakurai et al, 2005;Ichikawa and Yasunari, 2006;Love et al, 2011]. However, several fundamental issues still remain unexplained, such as the offshore shift mechanism, interactions with large-scale (longer-period) variations, and local orography effects, although they have been discussed by some previous studies [Ohsawa et al, 2001;Mapes et al, 2003;Ichikawa and Yasunari, 2008;Wu et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The relevant processes reported in previous studies include land breeze convergence [Houze et al, 1981], advection by background wind [Mori et al, 2004;Sakurai et al, 2009Sakurai et al, , 2011, self-replication of convective cells [Sakurai et al, 2009[Sakurai et al, , 2011, convergence of cold outflows produced by rainfall systems [Fujita et al, 2010], and gravity waves triggered by daytime heating of the mixed layer on land [Mapes et al, 2003] or convection on land [Love et al, 2011]. effects of seasonality on the diurnal propagation of precipitation systems.…”
Section: Introductionmentioning
confidence: 99%